Case report: Meningitis: a cause of reversible cerebral vasoconstriction syndrome? - Oukhai, Fida; Domigo, Valérie; Benzakoun, Joseph; Wolff, Michel; Ducros, Anne; Mas, Jean-Louis; Calvet, David (Frontiers in Neurology, 2023)
Introduction Reversible cerebral vasoconstriction syndrome (RCVS) is characterized by thunderclap headache and reversible cerebral arteries vasoconstriction. The pathophysiology remains unclear, but many triggers were reported. Case reports We reported two cases of patients with meningitis who developed RCVS confirmed by brain imaging. They presented clinical and CSF features of meningitis that are suspected to be infectious, but no agent was identified. Headache and artery irregularities were resolved with the improvement of CSF. Conclusion These cases suggest that in the context of meningitis, modification or atypical headaches should lead to brain imaging to rule out RCVS. We hypothesized that CSF inflammation may trigger cerebral arteries vasoconstriction.